Can the impacts of cold-water pollution on fish be mitigated by thermal plasticity?. Issue 1 (18th February 2020) - Parisi, M A; Cramp, R L; Gordos, M A; Franklin, C E
Abstract : Many Australian fish species are subject to thermal pollution from unseasonably cold water released from large storage dams. This study assessed the impacts and rate of physiological compensation to low temperatures following a simulated cold-water pollution event on juveniles of critically endangered silver perch ( Bidyanus bidyanus ). Abstract: Increasingly, cold-water pollution (CWP) is being recognised as a significant threat to aquatic communities downstream of large, bottom-release dams. Cold water releases typically occur during summer when storage dams release unseasonably cold and anoxic hypolimnetic waters, which can decrease the temperature of downstream waters by up to 16°C. Depending on the release duration, these hypothermic conditions can persist for many months. The capacity of ectothermic species to tolerate or rapidly adjust to acute temperature changes may determine the nature and magnitude of the impact of CWP on affected species. This study assessed the impacts of an acute reduction in water temperature on the physiological function and locomotor performance of juvenile silver perch ( Bidyanus bidyanus ) and examined their capacity to thermally compensate for the depressive effects of low temperatures via phenotypic plasticity. Locomotor performance ( U crit and U sprint) and energetic costs (routine and maximum metabolic rate) were measured at multiple points over a 10-week period following an abrupt 10°C drop in water temperature. We also measured the thermal sensitivity of metabolic enzymes from muscle samples taken from fish following the exposure period. Cold exposure had significant depressive effects on physiological traits, resulting in decreases in performance between 10% and 55%. Although there was partial acclimation of U crit ( 35% increase in performance) and complete compensation of metabolic rate, this occurred late in the exposure period, meaning silver perch were unable to rapidly compensate for the depressive effects of thermal pollution. The results of this study have substantial implications for the management of cold water releases from large-scale dams and the conservation of native freshwater fish species, as this form of thermal pollution can act as a barrier to fish movement, cause reduced recruitment, ecological community shifts and disruptions to timing and success of reproduction.